Satisfacción de los clientes en automóvil club del Ecuador Aneta. Agencia-Babahoyo. - Gómez Jácome, Xiomara Jelexny (2022)
Automóvil Club del Ecuador Aneta, is a company created as a learning school, whose intention is to train new drivers based on technical, mechanical and legal training that allows a good performance of the driver on the roads of the country. The objective of this case study is to analyze customer satisfaction in this company. The methodology used for the development of the research is descriptive, which in turn is qualitative and quantitative, where an interview was conducted with the manager of the agency in the city of Babahoyo, and a survey was conducted with the employees of the company with questions related to the subject of the case. The results of the investigation allowed determining that the satisfaction of the clients of Aneta Automóvil Club del Ecuador, Babahoyo Agency, is insufficient, that is to say, the users of the services offered by this company do not feel satisfied in reality, of those surveyed practically only 28% feel satisfied with the service, therefore, this company must improve. The case study allowed concluding that one of the problems that arises is the lack of personnel that generates discomfort and concerns to users because they are made to wait too long due to lack of personnel to attend them.